Song performance is a condition‐dependent dynamic trait honestly indicating the quality of paternal care in the bull‐headed shrike. (31st October 2018) - Nishida, Yuusuke; Takagi, Masaoki
Abstract : The good parent hypothesis in sexual selection predicts that if females can increase their fitness by mating with males who provide high‐quality parental care, then female preferences for male phenotypes honestly indicating the quality of paternal care will evolve. In order to test this hypothesis, we investigated correlations between male song, the timing of pair formation of males, male feeding rate, and reproductive success, in the bull‐headed shrike Lanius bucephalus (an altricial oscine passerine with biparental care). Analysis revealed that although the timing of pair formation was not correlated with most song characteristics (e.g. repertoire size), male morphological traits (e.g. tail length), or male territory size, it was negatively correlated with male singing tempo (i.e. the number of notes uttered per second). Those males that sang at higher speeds were in better body condition (i.e. body mass standardized by tarsus length 3 was higher), fed their chicks frequently during the nestling period, and raised heavy chicks. These results show that in the bull‐headed shrike male singing tempo is a condition‐dependent dynamic trait honestly indicating the quality of paternal care, and strongly supports the good parent hypothesis.